Clean-up Drive System as Watershed Conservation at Saran River, Laguna, Philippines : Implications for Perception of Residents - Nurul Amri Komarudin; Justine angelo Lacson; Elaiza Christina Toribio; Peter Hasudungan; Ramon Jr. Maulit; Arlene Talaña; Yahya Shafiyuddin Hilmi; Leonardo M. Florece; Erica Paula Yohanon (International Journal of Hydrological and Environmental for Sustainability, 2023)
Barangay Malinta has a regular garbage waste collection schedule. Biodegradable wastes are collected on Mondays, Wednesdays, and Fridays while non-biodegradable wastes are collected on Saturdays. The barangay is compliant to the RA 9001 (Solid Waste Management) however, they do not have a Material Recovery Facility (MRF). The absence of MRF is due to geographical location of the barangay which prohibits the establishment of the MRF facility due to its proximity to Laguna bay. The study aims to determine the perception of the respondents regarding the Clean-up Drive activities at the Saran River and to integrate it with the recommendations to aid in the improvement of the cleaning efforts for the said river, particularly at Barangay Malinta, Los BaÃ±os, Laguna, Philippines. Random sampling was used to identify residents to be included in the survey. The data were analyzed using percentage and mean. The results showed that the level of awareness among respondents residing Saran river is high. In terms of attitude, most of them strongly agreed that there will be a clean-up in the river and penalized those who will throw their waste in the river, most of the respondents are satisfied with the on-going river clean-up and optimistic that the river can still be cleaned and revived, and most of the respondents are willing to contribute amount and will be paid in the barangay as funding to river clean-up.